Fourth International Topical Meeting on High Temperature Reactor Technology, Volume 2 2008
DOI: 10.1115/htr2008-58336
|View full text |Cite
|
Sign up to set email alerts
|

A Safety Re-Evaluation of the AVR Pebble Bed Reactor Operation and Its Consequences for Future HTR Concepts

Abstract: The AVR pebble bed reactor (46 MWth) was operated 1967-88 The AVR primary circuit is heavily contaminated with metallic fission products which create problems in current dismantling .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 7 publications
(12 reference statements)
2
48
0
Order By: Relevance
“…The widely published advantageous features [1,8,12,40] of pebble bed HTRs are out of the scope of this paper. More detailed studies to these AVR/HTR problems are found in [4].…”
Section: Introductionmentioning
confidence: 99%
“…The widely published advantageous features [1,8,12,40] of pebble bed HTRs are out of the scope of this paper. More detailed studies to these AVR/HTR problems are found in [4].…”
Section: Introductionmentioning
confidence: 99%
“…The dust production estimate of 6.5 to 6.7 grams per year is very low compared to an estimated of 3 kg per year in the German AVR (Moormann, 2009). …”
Section: Dust Mass Predictionmentioning
confidence: 99%
“…Several reports, such as those by Dr. Moormann, 37 the Jülich Institut für Reaktorwerkstoffe GmbH, 38 36 and the International Atomic Energy Agency (IAEA) discuss the fission products of the elements. During the time of decommissioning and fuel removal of AVR, Dr. Rainer Moormann developed a reevaluation of the AVR.…”
Section: Pebble Bed Fuel Performance (Avr)mentioning
confidence: 99%
“…This damage mechanism leads to SiC damage above 2200°C, during heating at 50°C per hour. 37 Lessons Learned: Previous work done for the AVR regarding fission product mobility and high temperature fuel degradation could benefit the NGNP fuel design. NGNP fuel experiments are evaluating fuel temperatures in excess of 1600°C and rapid temperature gradients.…”
Section: Pebble Bed Fuel Performance (Avr)mentioning
confidence: 99%